Research Protocol: The practice of medical humanitarian emergency: ethnography of practitioners’ response to nutritional crisis - Stellmach, D (Medecins sans Frontieres, 2014)
Overall Aim: To describe and understand the human and technological factors that contribute to the constitution of emergency as a named and actionable entity in the context of medical humanitarianism. Primary Objective: To describe how individual and institutional attitudes, tools, discretion and practices influence identification and response to emergency. Secondary Objective: To document ambiguities, uncertainties or structural barriers that impede the identification of and response to emergency.